2022
DOI: 10.3390/foods11060795
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics Changes of Microorganisms Community and Fermentation Quality in Soybean Meal Prepared with Lactic Acid Bacteria and Artemisia argyi through Fermentation and Aerobic Exposure Processes

Abstract: This study evaluated the effects of Lactiplantibacillus plantarum subsp. plantarum ZA3, Artemisia argyi and their combination, on the fermentation characteristics, microbial community, mycotoxins and crude flavonoids content of fermented soybean meal during fermentation (under anaerobic conditions) and aerobic exposure (under aerobic conditions). The results showed that ZA3, Artemisia argyi and ZA3+ Artemisia argyi groups had lower pH values and higher lactic acid concentrations compared with controls, and add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…This observation indicated that ZA3 and AA can change fungi community when environment changes from anaerobic to aerobic. It is possible that acid-tolerant bacteria still dominate the bacterial community in the early period of aerobic exposure, and the variation of microbial community might explain the difference in fermentation quality [ 15 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This observation indicated that ZA3 and AA can change fungi community when environment changes from anaerobic to aerobic. It is possible that acid-tolerant bacteria still dominate the bacterial community in the early period of aerobic exposure, and the variation of microbial community might explain the difference in fermentation quality [ 15 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of bacteria involved in lactic acid fermentation belong to the Firmicutes. However, once the WCCS silage was exposed to oxygen, Firmicutes were gradually replaced by Proteobacteria, which might be because an increase in pH and decrease in organic acids are not beneficial to the proliferation of Firmicutes [ 15 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations